INFLUENCE OF THERMAL PROCESSING ON THE STRUCTURE AND CHARACTERISTICS OF ECONOMICALLY-ALLOYED HIGH-STRENGTH CAST IRON - A. N. Krutilin; N. I. Bestuzhev; V. A. Stefanovich; M. I. Kurbatov (Литьë и металлургия)
Influence of thermal processing on structure and characteristics o f economically-alloyed high-duty cast iron is shown.